Detection of mental disorders other than depression with the Edinburgh Postnatal Depression Scale in a sample of pregnant women in northern Mexico - Cosme Alvarado-Esquivel; Antonio Sifuentes-Alvarez; Carlos Salas-Martinez (Mental Illness)
We sought to evaluate the capacity of the Edinburgh Postnatal Depression Scale (EPDS) in discriminating mental disorders other than depression in pregnant women in northern Mexico. Three hundred pregnant women attending prenatal consultations in a public hospital in Durango City, Mexico submitted a validated EPDS and were examined for mental disorders other than depression using the Diagnostic and Statistical Manual of Mental Disorders - 4th Ed. (DSM-IV) criteria. Sensitivity and specificity of cut-off points of the EPDS, and positive and negative predictive values were calculated. Of the 300 pregnant women studied, 21 had mental disorders other than depression by the DSM-IV criteria. The best EPDS score for screening mental disorders other than depression was 8/9. This threshold showed a sensitivity of 52.4%, a specificity of 67.0%, a positive predictive value of 11.5%, a negative predictive value of 95.4%, and an area under the curve of 0.643 (95% confidence interval: 0.52-0.76). The EPDS can be considered for screening mental disorders other than depression in Mexican pregnant women whenever a cut-off score of 8/9 is used. However, the tool showed small power to separate pregnant women with and without mental disorders other than depression.